Virtual Tour Design and Implementation Kiara Artha Park Bandung Tourism Location - Kurniawan, Rudi; Ramadhan, Teddy Muhammad (CoreID Journal, 2023)
Based on the observations made of Kiara Artha Park Bandung, it is known that no interactive media can introduce the description of the situation and environment in Kiara Artha Park to outsiders. When there are restrictions on visit policies due to lockdown, tourists or the public cannot directly visit the location. One of the alternative solutions above is to build a Virtual Tour model that can provide an overview of Kiara Artha Park if tourists need help to come directly to the location. The research method used is the MDLC (Multimedia Development Life Cycle) method, suitable for designing and developing a multimedia-based application that combines elements such as images, sound, video, animation, and others. Tools used for image media are GoPro Max 360 cameras, and the application used is Quik with photo processing using 3Sixty. The result of the construction of this Virtual Tour is to map and describe the overall condition of Kiara Artha Park with 360-degree image media. The development of the structure of this Virtual Tour is to map and describe the general requirement of Kiara Artha Park with 360-degree image media.